A distal heterochromatic block displays centromeric activity when detached from a natural centromere. - Platero, J.S.; Ahmad, K.; Henikoff, S. (Molecular Cell, 1999)
We repeatedly released a distal block of heterochromatin lacking a natural centromere in mitotic cells and assayed its segregation. At anaphase, control acentric fragments typically remained unoriented between daughter nuclei and were subsequently lost. Fragments containing the brownDominant (bWD) heterochromatic element displayed regular anaphase movement upon release. These fragments were found to segregate and function based on both cytological and phenotypic criteria. We also found that intact bWD-containing chromosomes normally display occasional dicentric behavior, suggesting that bWD has centromeric activity on the intact chromosome as well. Our findings suggest that centromere competence is innate to satellite-containing blocks of heterochromatin, challenging models for centromere identity in which competence is an acquired characteristic.